Impact of the EU Directives on Defendant's Rights on the Macedonian Criminal Procedure: Directive on the Right to Information in Criminal Proceedings and Directive on the Right to Interpretation and Translation in Criminal Proceedings - Ilic Dimoski, Divna /Misoski, Boban (Faculty of Law Iustinianus Primus Skopje, 2020)
The authors of this paper discuss the impact of the EU Directive 2012/13/EU on the right to information in criminal proceedings and Directive 2010/64/EU on the right to interpretation and translation in criminal proceedings to the Macedonian criminal procedure system. They refer to the common minimum standards set in the field of information about rights and about the accusation which must be given to persons suspected or accused of having committed a criminal offence, as well as the right to interpretation and translation, to enhance mutual trust among the Member States. The benchmark these Directives establish is projected trough the complex of several rights. Firstly, there is the right to information about rights for suspects or accused persons. Additional rights are recognized when suspects are arrested and detained in which case information about applicable procedural rights should be given by means of a written Letter of Rights drafted in an easily comprehensible manner to assist those persons in understanding their rights. Subsequent is the right to access to the materials of the case, conditions and limitations to its exercise and as well as the right to provide information to suspects or accused persons where necessary, with translations or interpretation into a language that they understand. Moreover, the authors are evaluating whether these standards are properly incorporated into the Law on Criminal Procedure and they provide substantial recommendations for additional changes and amendments to the law in order to achieve the abovementioned criteria into Macedonian national law.
Keywords: EU directive, suspect, right to information, Letter of Rights, right to interpretation, right to translation, criminal procedure, Republic of North Macedonia